The Measurement and Dimensionality of Mobile Learning Systems Success: Two-Stage Development and Validation. (July 2017) - Lin, Hsin-Hui; Wang, Yi-Shun; Li, Ci-Rong; Shih, Ying-Wei; Lin, Shin-Jeng
The main purpose of this study is to develop and validate a multidimensional instrument for measuring mobile learning systems success (MLSS) based on the previous research. This study defines the construct of MLSS, develops a generic MLSS instrument with desirable psychometric properties, and explores the instrument's theoretical and practical applications. By analyzing data from a calibration sample ( n = 241) and a validation sample ( n = 209), this study proposes a 6-factor, 25-item MLSS instrument. This empirically validated instrument will be useful to researchers in developing and testing mobile learning theories, as well as to educators in understanding MLSS from students' perspective and promoting the use of mobile learning systems.